Configuring a mini-laboratory and desktop 3-axis parallel kinematic milling machine - Zivanovic, Sasa (Strojniški vestnik, 2015)
Configuring new machine tools is a complex task that involves the use of a large range of conceptions, methods, models, virtual prototypes and simulations. This paper presents a methodology for configuring a new machine tool to the level of a virtual prototype by using CAD configurator Pro/WEB.Link and a top-down approach. This methodology is explained via an example of the development of a mini-laboratory and desktop 3-axis parallel kinematic milling machine (PKMM). The results are two variants of the virtual prototype and one real world prototype. The configured virtual prototypes are used for the verification of the machining program and programming system using machining simulation in the CAD/CAM environment. The mini-laboratory and desktop 3-axis PKMM has been verified by the successful machining of test workpieces.
Keywords: CAD konfiguratorji; konfiguriranje; obdelovalni stroji; pristop od zgoraj navzdol; simulacije obdelave